An Investigation for Benefits of Cyber-Physical Systems in Higher Education Courses - Yetis, Hasan; Baygin, Mehmet; Karakose, Mehmet (Ieee, 2016)
With being used of steam powered machines in manufacturing, first industry revolution launched. After that, industry has continued to develop with the aid of engineering education in universities. The developed industry brought along new searching topics and also new engineering areas. With the adaptation of industry and engineering education new revolutions occurred. Today, industry 4 is actualizing with being used cyber-physical systems in manufacturing. In this paper the need for cyber-physical systems in higher engineering education, and its advantages are represented.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: Cyber Physical Systems; Industry 4.0; Higher Education; Curriculum